2016
DOI: 10.1242/bio.019802
|View full text |Cite
|
Sign up to set email alerts
|

A lipidomics study reveals hepatic lipid signatures associating with deficiency of the LDL receptor in a rat model

Abstract: The low-density lipoprotein receptor (LDLR) plays a critical role in the liver for the clearance of plasma low-density lipoprotein (LDL). Its deficiency causes hypercholesterolemia in many models. To facilitate the usage of rats as animal models for the discovery of cholesterollowering drugs, we took a genetic approach to delete the LDLR in rats aiming to increase plasma LDL cholesterol (LDL-C). An LDLR knockout rat was generated via zinc-finger nuclease technology, which harbors a 19-basepair deletion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…They concluded that LDL receptors play a major role in the catabolism of remnant particles. Wang, H. Y. et al [ 10 ] reported the generation of LDLR-KO rat with disruption of exon 7, the deletion of the LDLR elevated total cholesterol and total triglyceride in the plasma, and caused a tenfold increase of plasma LDL and a fourfold increase of plasma VLDL on high cholesterol diet. In this study, mutations of the founder rabbit LDLR gene can be divided into two kinds: frame-shift mutation and deletion/insertion of several amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that LDL receptors play a major role in the catabolism of remnant particles. Wang, H. Y. et al [ 10 ] reported the generation of LDLR-KO rat with disruption of exon 7, the deletion of the LDLR elevated total cholesterol and total triglyceride in the plasma, and caused a tenfold increase of plasma LDL and a fourfold increase of plasma VLDL on high cholesterol diet. In this study, mutations of the founder rabbit LDLR gene can be divided into two kinds: frame-shift mutation and deletion/insertion of several amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of different genes causes hypercholesterolemia in many models, including mice [ [7] , [8] , [9] ], rats [ 10 , 11 ], and pigs [ 12 ]. Analysis of these animal models shows that changes in systemic lipid metabolism and plasma lipoproteins, and the formation of atherosclerotic lesions are variably affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since untreated FH significantly accelerates cardiovascular diseases (CVD), such as myocardial infarction, carotid atherosclerosis and coronary artery disease (CAD), it is considered as a major public health burden . Homozygous and heterozygous FH patients are characterized by extremely high, declining to moderate cholesterol levels . Approximately 1 per 200–300 persons worldwide is affected by heterozygous FH .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Homozygous and heterozygous FH patients are characterized by extremely high, declining to moderate cholesterol levels. 11 Approximately 1 per 200-300 persons worldwide is affected by heterozygous FH. 12 However, the homozygous FH occurs more rarely, with an estimated prevalence of 1/160,000 to 1/300,000.…”
Section: Introductionmentioning
confidence: 99%